Schwann cells-derived exosomes promote functional recovery after spinal cord injury by promoting angiogenesis - Huang, Jiang-Hu; Chen, Yong-Neng; He, Hang; Fu, Chun-Hui; Xu, Zhao-Yi; Lin, Fei-Yue (Frontiers in Cellular Neuroscience, 2023)
Exosomes are small vesicles that contain diverse miRNA, mRNA, and proteins that are secreted by multiple cells, and play a vital function in cell-cell communication. Numerous exosomes produced by cells have been demonstrated to be protective against spinal cord injury (SCI). This study aims to investigate the neuroprotective effect of Schwann cells-derived exosomes (SCs-Exos) on spinal cord injury. We found that SCs-Exos can be taken directly by brain-derived endothelial cells.3 (bEnd.3 cells), and promoted to proliferate, migrate and form bEnd.3 tube. Additionally, our results showed that the pro-angiogenesis molecules, Integrin-β1 were highly expressed in SCs-Exos. moreover, we used special shRNA technology to investigate the role of Integrin-β1 in mediating the effect of SCs-Exos-induced angiogenesis on bEnd.3 cells. We observed that, the pro-angiogenic effect of SCs-Exos on bEnd.3 cells were suppressed by inhibiting the expression of integrin-β1 in SCs-Exos. In the SCI model, we found that SCs-Exos attenuated tissue damage and improved functional recovery after SCI. By using immunofluorescence staining, we observed that SCs-Exos treatment promoted angiogenesis in SCI, and integrin-β1 was required to promote angiogenesis. In conclusion, our results indicate that SCs-Exos promote angiogenesis by delivering integrin-β1 and may serve as a promising novel therapeutic agent for enhancing neurological functional recovery after SCI.